Growing Old in a Valley of Northern Italy: Informal Care Networks in a Shifting Welfare Scenario - Roberta Clara Zanini; Amalia Campagna; Matteo Volta (Revue de Géographie Alpine)
This contribution explores the multifaceted care practices of Chiusella Valley, a Piedmontese valley nestled in the Italian Graian Alps, house of approximately 5000 inhabitants. Over the past 50 years, Chiusella Valley has undergone several shifts: it went from being a mining centre to serving as a labour pool for nearby manufacturing centres, then underwent a process of deindustrialization that led to a steady decline in population and personal services. In the last decade, signs of a trend reversal have been detected, driven by return migrations and by the influx of newcomers from urban areas. Despite being categorized as a marginal area due to the lack of infrastructure in public transport, education and healthcare systems, Chiusella Valley today boasts a vibrant social fabric with over 50 associations and mutualistic realities. Amidst these dynamics, an ongoing multidisciplinary research-action project known as “Laboratorio Valchiusella”, spearheaded by the University of Turin since 2018, aims to integrate nursing education with socio-anthropological fieldwork, fostering a deep understanding of the valley’s healthcare needs and the intricacies of community care after the Covid-19 pandemic. Against this backdrop, an ethnographic comprehensive investigation into informal caregiving experiences in Chiusella Valley was undertaken in 2022, seeking to comprehend the intimate nuances of caregiving within the context of institutional deficits, emphasizing the significant role played by family members and non-professional volunteers in enabling elderly people to navigate old age and illnesses. Therefore, based on the findings of the fieldwork and employing an anthropological and sociological outlook, this paper aims to explore administrative and organizational changes within the Italian National Health Service and mountain territories on a local scale. The article intends to show how social, micropolitical and territorial characteristics of Chiusella Valley affect the caregiving activities, connecting the practices of care to the political and historical dynamics that determined the relations of this territory with public health services.